The political economy of academic publishing: On the commodification of a public good - Stephan Pühringer; Johanna Rath; Teresa Griesebner (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2020)
This paper provides an institutional and empirical analysis of the highly concentrated market of academic publishing, characterized by over-proportionally high profit margins for publishing companies. The availability of latest research findings is of primary importance for researchers, universities and politicians alike. Open access (OA) publication provides a promising, yet costly solution to overcome this problem. However, in this paper we show that OA publication costs are an important, but by far not the only way for academic publishers to gain access to public funding. More precisely, our study provides a comprehensive overview of the channels through which public expenditure benefits large academic publishing companies. Furthermore, we offer the results of an explorative case study, where we estimate the annual financial flows of public expenditures in Austria for the field of social sciences, based on our four-channel-model. These expenditures add up to about 66.55 to 103.2 million exteuro a year, which amounts to a fourth of total public funding for this field. Against this background, we aim to open up the debate whether, and to what extent public subsidies are justified for economically successful companies.
Keywords: 330; academic publishers; academic publishing; open access; social sciences; Austria